Discoursing disasters vulnerability and gaps in rationalities - Rodriguez, Agustin Martin G. (Philippine studies : historical and ethnographic viewpoints, 2016)
"Although Filipinos live with the realities of recurring extreme weather occurrences, some are more vulnerable to disasters than others. Using discourse theory, this article seeks to understand how a community's vulnerability is connected to the marginalization of its rationality. It traces the conditions brought about by Westerization that created and sustained the vulnerability of the marginalized. It explores the gaps that exist in the rationalities of policy makers and disaster-vulnerable persons and the consequences of these gaps for the vulnerable in order to argue for the need to found genuine disaster risk reduction (DRR) programs on the principles of inclusive discourse."